The Effect of Perceived Distance on Purchase Intention: A Case Study of E-Commerce in Indonesia (The Indonesian Journal of Business Administration, 2021)
During this Covid-19 pandemic, there is a surge in e-commerce and the increasing number of e-commerce deliveries in 10 years to 8 weeks. Gross merchandise value (GMV) in Indonesia reached US $ 40 billion in 2020, the third highest in the world. There are many choices of e-commerce platforms available, yet not all e-commerce platforms can compete equally. Lack of consumer trust is a major obstacle for e-commerce to thrive. The challenge of e-commerce in Indonesia is a large country with many islands, so the distance between buyers and sellers can be very far. Therefore, the researcher wants to see the extent to which the perception of distance affects buyer trust and will influence customers to buy the product through e-commerce. This study uses a quantitative method by distributing questionnaires to Indonesians who have purchased goods through e-commerce with total respondents 312. The results show that buyer’s trust in e-commerce greatly influences consumers to buy through e-commerce products, spatial distance is the distance that most influences trust and shipping costs greatly influences e-commerce customer purchase intentions. The final result of this research is a marketing strategy in the form of a 4p marketing mix. The products sold must be diverse and their availability is guaranteed. The price must compete with other e-commerce and there are variations in shipping prices. The promotions are discount voucher, massive discount on certain products for limited time, and discount shipping voucher. Purchase products online but it is advisable to build a warehouse on each island. Keywords: E-Commerce, Psychological Distance, Trust, Purchase Intention, Marketing Mix